Boolean Simplification

I've been attempting to streamline this formula:

$Y = (¬AB + ¬C)(¬A + ¬D)$

. right into this formula.

$Y = ¬A¬C + ¬C¬D + ¬AB$

Unfortunately I maintain entering circles with increasing and also decreasing the booleans. Any kind of pointers or suggestions? Many thanks.

0
2019-05-18 23:57:53
Source Share
Answers: 1

Use the adhering to simplification:

$\neg AB(\neg A + \neg D) = \neg AB\neg A + \neg AB\neg D = \neg AB + \neg AB\neg D = \neg AB$.

0
2019-05-21 12:06:30
Source